Respuesta :

❤❤❤❤❤❤❤❤❤❤❤❤❤❤❤

[tex]b = 9 {n}^{2} + 7[/tex]

[tex]a = 3n + 4[/tex]

-----------------------------------------------------------

[tex] {a}^{2} = ( {3n + 4})^{2} [/tex]

[tex] {a}^{2} = 9 {n}^{2} + 24n + 16[/tex]

________________________________

[tex]b = 9 {n}^{2} + 7[/tex]

[tex]b = 9 {n}^{2} + 24n - 24n + 7 + 9 - 9 \\ [/tex]

[tex]b = (9 {n}^{2} + 24n + 16) - 24n - 9 - 23 + 23 \\ [/tex]

[tex]b = (9 {n}^{2} + 24n + 16) - (24n + 32) + 23 \\ [/tex]

[tex]b = ({3n + 4})^{2} - 8(3n + 4) + 23 [/tex]

[tex]b = {a}^{2} - 8a + 23[/tex]

Thus the correct answer is ( B ) .

❤❤❤❤❤❤❤❤❤❤❤❤❤❤❤